2014
DOI: 10.1177/1541931214581316
|View full text |Cite
|
Sign up to set email alerts
|

Is “chart junk” useful? An extended examination of visual embellishment

Abstract: Although many well-cited theories or guidelines for visualization design advocate 'minimalism', designers tend to include a wide variety of visual embellishments in their charts. Researchers have examined the effects of visual embellishment on comprehension and memorability of charts under specific conditions, such as charts with a small number of data points that were viewed with no time limit (Bateman et al., 2010). This paper extends previous studies and investigates the effects of visual embellishment give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 5 publications
0
30
0
Order By: Relevance
“…The assessment of "concept grasping" by Borgo et al (2012) was similar to our assessment of theme recall, and the findings align as previously discussed. Recall of chart value details is difficult, and our study did not find differences due to While some of these studies (Bateman et al, 2010;Borkin et al, 2013;Li and Moacdieh, 2014) look at illustrative graphics and elaborate infographic embellishments more similar to Holmes (1984), others have investigated more minor manipulations and stylistic enhancements (Borgo et al, 2012;Haroz et al, 2015). Our research tends toward the side of more limited embellishments in an attempt to preserve the underlying visual encodings of data, though our custom created embellishments may provide a somewhat greater degree of enhancement while maintaining high experimental control for the presented study.…”
Section: Towards a Greater Understanding Of Memorability And The Desimentioning
confidence: 39%
“…The assessment of "concept grasping" by Borgo et al (2012) was similar to our assessment of theme recall, and the findings align as previously discussed. Recall of chart value details is difficult, and our study did not find differences due to While some of these studies (Bateman et al, 2010;Borkin et al, 2013;Li and Moacdieh, 2014) look at illustrative graphics and elaborate infographic embellishments more similar to Holmes (1984), others have investigated more minor manipulations and stylistic enhancements (Borgo et al, 2012;Haroz et al, 2015). Our research tends toward the side of more limited embellishments in an attempt to preserve the underlying visual encodings of data, though our custom created embellishments may provide a somewhat greater degree of enhancement while maintaining high experimental control for the presented study.…”
Section: Towards a Greater Understanding Of Memorability And The Desimentioning
confidence: 39%
“…In contrast, we test for unprompted recall of the data in the visualizations. Bateman's study has been somewhat controversial, and Li et al [LM14] recently reported a replication, limiting their selection to those charts that consisted of data sets with 10 or more observations. They found that the presence of a time limit affected comprehension and short‐term recall performance, while the type of chart significantly affected short‐term recall.…”
Section: Related Workmentioning
confidence: 99%
“…For the long term recall condition, phase three occurred four days after phase two. We chose the length of our long‐term recall condition as in previous long‐term evaluations, e.g., Li et al [LM14].…”
Section: Preliminariesmentioning
confidence: 99%
“…Bateman et al [15] conducted a study to test the comprehension and recall of charts using an embellished version and a plain version. Bateman's study has been somewhat controversial, and Li et al [62] recently reported a replication, limiting their selection to those charts that consisted of datasets with 10 or more observations. They found that the presence of a time limit affected comprehension and short-term recall performance, while the type of chart significantly affected short-term recall.…”
Section: Measures Beyond the Standardmentioning
confidence: 99%